Microscopy-based assay for semi-quantitative detection of SARS-CoV-2 specific antibodies in human sera - Pape, Constantin; Remme, Roman; Wolny, Adrian; Olberg, Sylvia; Wolf, Steffen; Cerrone, Lorenzo; Cortese, Mirko; Klaus, Severina; Lucic, Bojana; Ullrich, Stephanie; Anders-Ößwein, Maria; Wolf, Stefanie; et al. (Bioessays, 2021)
Emergence of the novel pathogenic coronavirus SARS-CoV-2 and its rapid pandemic spread presents challenges that demand immediate attention. Here, we describe the development of a semi-quantitative high-content microscopy-based assay for detection of three major classes (IgG, IgA, and IgM) of SARS-CoV-2 specific antibodies in human samples. The possibility to detect antibodies against the entire viral proteome together with a robust semi-automated image analysis workflow resulted in specific, sensitive and unbiased assay that complements the portfolio of SARS-CoV-2 serological assays. Sensitive, specific and quantitative serological assays are urgently needed for a better understanding of humoral immune response against the virus as a basis for developing public health strategies to control viral spread. The procedure described here has been used for clinical studies and provides a general framework for the application of quantitative high-throughput microscopy to rapidly develop serological assays for emerging virus infections.